Product Quality Dynamics and Brand Image as Determinants of Local Coffee Consumers' Purchasing Decisions - Rendy Suhenda MANURUNG; Kemal Budi MULYONO (International Journal of Environmental, Sustainability, and Social Science, 2025)
The rapid growth of Indonesia’s specialty coffee industry has intensified competition, positioning product quality and brand image as critical factors influencing consumer purchase behavior. Although these variables have been extensively studied, prior research remains dominated by global brand contexts, offering limited insights into local coffee shop dynamics where consumer decisions are shaped by unique perceptions of quality and brand experience. This study investigates the effects of product quality and brand image on purchase decisions among Poin Coffee Taman Siswa, Sekaran consumers, using the Theory of Reasoned Action (TRA) as the theoretical foundation. TRA suggests that purchase behavior is driven by behavioral intentions, which arise from attitudes shaped by evaluative beliefs about a product. A quantitative explanatory design was applied, involving 100 respondents selected via purposive sampling. Data were collected through a Likert-scale questionnaire and analyzed using validity and reliability tests, descriptive statistics, and multiple regression analysis. The results indicate that product quality and brand image have positive and significant effects both individually and simultaneously on purchase decisions. This study reinforces TRA’s applicability in explaining consumer attitudes and suggests future studies incorporate moderating variables such as word of mouth, pricing, and promotion.